Overlapping states of AWGS muscle dysfunction and inverse feasibility of ADL recovery by rehabilitation in older inpatients - Masashi Yamashita; Hiroaki Obata; Kentaro Kamiya; Atsuhiko Matsunaga; Kazuki Hotta; Tohru Izumi (Scientific Reports, 2022)
Abstract Rehabilitation based on guided walking is effective to recover activity of daily living (ADL) in frail older adults, even octogenarians. However, muscle dysfunction obviously reflects disability, and few studies have focused on ADL recovery by rehabilitation. We employed the state of muscle dysfunctions proposed by the Asian Working Group for Sarcopenia (AWGS) in 2019 and attempted to clarify the relation between the overlapping dysfunctions and the feasibility of ADL recovery after rehabilitation. In total, 297 frail older patients (the mean age: 82.8 years, 46.1% of patients were male) participated in a walking-guided rehabilitation program to achieve the goal of ambulatory discharge. Muscle dysfunction was categorized by four standardized methods at the start of rehabilitation (grip strength, gait speed, time of five sit-to-stand, and short physical performance battery: SPPB), according to the AWGS proposal. ADLs were monitored by Barthel index before admission, at the start of rehabilitation, and at discharge. At least one dysfunction was present in 95.3% of patients. If a single patient had three or more muscle dysfunction, the ADLs recovery was significantly limited (interaction: p < 0.05). The overlapped counts of AWGS muscle dysfunction helps to predict inverse feasibility of ADL recovery in frail older patients through rehabilitation.